Cases detected with sildenafil/tadalafil/vardenafil in autopsies performed in Muğla: retrospective evaluation - Mutlu, Emre; Ersoy, Burcu; Balcı, Yasemin; Ilıngı, Ufuk (The Bulletin of Legal Medicine, 2025)
Objective: In this study, it was aimed to discuss the cases that were detected with phosphodiesterase 5 (PDE-5) inhibitors in autopsies performed, the mechanisms that may affect death, the aspects to be paid attention and protective measures in autopsy of these cases, and to investigate whether the use of PDE-5 inhibitors has cardiac side effects. Materials and Methods: Cases in which PDE-5 inhibitors were found in body fluids in toxicological examinations among autopsies performed in the 8-year period between January 01, 2013 and December 31, 2023 in Mugla Forensic Medicine Branch Office were retrospectively evaluated. Results: Sildenafil/vardenafil/tadalafil were detected in 49 (0.9%) of 5,277 autopsy cases. Sudden/suspicious deaths were the most common reason for sending the cases to autopsy. This was followed by drowning, traffic accidents and hangings, respectively. The most common cause of death in cases using PDE-5 inhibitors was atherosclerotic cardiovascular disease/ myocardial infarction (n:22, 44.8%). Conclusion: In our study, it was determined that more than 44.8% of the cases with PDE-5 inhibitors in the autopsy had cardiovascular diseases. It suggests that PDE-5 inhibitors may have caused risky cardiac side effects. It is considered that the present study will contribute to the literature in terms of showing the cardiac side effects of PDE-5 inhibitor.
Keywords: Postmortem toxicology, Sildenafil, Autopsy